Optimal Control of Droop Controlled Inverters in Islanded Microgrids. Issue 30 (2015) - Sahyoun, S.; Djouadi, S.M.; Shankar, M.
Abstract: For an islanded microgrid modeled by a Kuramoto oscillators nonlinear model, we design the distributed optimal controller using the maximum principle optimization theory. We first quantify synchrony in terms of phases and droop coefficients at the inverters in the microgrid and then we maximize it. We prove that the solution of the distributed optimal control problem exists and we find it. We evaluate performance in a simulation case.